2001
DOI: 10.1179/135100001101536382
|View full text |Cite
|
Sign up to set email alerts
|

Free radical generation in the toxicity of inhaled mineral particles: the role of iron speciation at the surface of asbestos and silica

Abstract: Free radical generation at the particle/biological fluid interface is one of the chemical processes that contributes to pathogenicity. In order to investigate the role played by iron, fibres of crocidolite asbestos have been modified by thermal treatments to alter their surface iron content. Two radical mechanisms, HO* from H2O2 and cleavage of a C-H bond, which are both active on the original fibres, have been tested on the modified fibres. C-H cleavage is dependent on Fe(II) abundance and location and is sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 36 publications
(47 reference statements)
2
35
0
Order By: Relevance
“…[8,9,19] Iron chelators reduce free radical release from asbestos, [5,14] although no direct correlation may be established between the amount of iron removal and the reactivity at the fiber surface, which depends not only on the amount of surface iron but also on its coordination and oxidation state and on the fiber micromorphology. [15,27,32,33] The incubation with F. oxysporum, similarly to the treatment with chelators, causes a decrement in HOC release, with some differences among the different asbestos types examined. In the case of crocidolite and chrysotile, iron removal by the fungus fully blunted HOC radical activity.…”
Section: Discussionmentioning
confidence: 93%
“…[8,9,19] Iron chelators reduce free radical release from asbestos, [5,14] although no direct correlation may be established between the amount of iron removal and the reactivity at the fiber surface, which depends not only on the amount of surface iron but also on its coordination and oxidation state and on the fiber micromorphology. [15,27,32,33] The incubation with F. oxysporum, similarly to the treatment with chelators, causes a decrement in HOC release, with some differences among the different asbestos types examined. In the case of crocidolite and chrysotile, iron removal by the fungus fully blunted HOC radical activity.…”
Section: Discussionmentioning
confidence: 93%
“…[11b] In the first mechanism, generally described as a Fenton-like reaction [Equation (1 a)] that occurs at the fibre surface, [19] H 2 O 2 reacts with ferrous iron ions:…”
Section: Resultsmentioning
confidence: 99%
“…Following a well-established technique described in previous studies, [19] the nature and quantity of the stabilised radical was measured by means of electron paramagnetic resonance (EPR) spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Thus iron is not likely to be the main responsible for the oxidative stress exerted by quartz in our experiments. Experiments with pure quartz and iron-deprived quartz dusts have already shown that hydroxyl radicals can be generated in the absence of trace iron at the crystal surface (29). We think that our data suggest a new mechanism of silica-evoked oxidative stress, wherein particles induce oxidative stress also by inhibiting one of the main antioxidant pathways of the cell.…”
Section: Discussionmentioning
confidence: 79%